Ionic liquid compound, solid-state electrolyte, and battery

CN122916894APending Publication Date: 2026-10-16THE HONG KONG POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610866557.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-16
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0002]随着电动汽车、3C电子及储能等领域对高能量密度电池需求的持续增长,传统锂离子电池因采用碳酸酯类有机电解液,在过充、碰撞、内短路等滥用条件下极易发生电解液分解、热失控

Benefits of technology

本发明的离子液体化合物作为添加剂,具有蒸汽压低、温度适应性宽、电化学窗口宽、化学与电化学稳定性良好、绿色环保等优点。此外,能显著提升电池的安全性、界面稳定性和电化学性能,有利于形成富含无机的电解质/电极界面层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916894A_ABST
    Figure CN122916894A_ABST
Patent Text Reader

Abstract

The application provides an ionic liquid compound, a solid electrolyte and a battery. The ionic liquid compound has a structure shown in formula I; the ionic liquid compound of the application has the advantages of low vapor pressure, wide temperature adaptability, wide electrochemical window, good chemical and electrochemical stability, green environmental protection and the like as an additive. In addition, the ionic liquid compound can significantly improve the safety, interface stability and electrochemical performance of the battery, and is beneficial to the formation of an inorganic-rich electrolyte / electrode interface layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to an ionic liquid compound, a solid electrolyte, and a battery. Background Technology

[0002] With the continued growth in demand for high-energy-density batteries from electric vehicles, 3C electronics, and energy storage, traditional lithium-ion batteries, which use carbonate-based organic electrolytes, are highly susceptible to electrolyte decomposition and thermal runaway under abuse conditions such as overcharging, impact, and internal short circuits. Especially as battery specific capacity increases significantly, side reactions such as lithium deposition at the negative electrode and oxygen release at the positive electrode intensify. To meet the development needs of next-generation high-energy-density and high-power-density rechargeable batteries, solid-state lithium batteries, by replacing organic electrolytes with solid electrolytes, fundamentally eliminate risks such as leakage and fire. They also possess the ability to suppress lithium dendrite penetration and avoid internal short circuits, exhibiting excellent electrochemical stability, mechanical flexibility, and wide temperature range adaptability. Therefore, developing high-voltage resistant solid electrolytes and constructing all-solid-state lithium rechargeable batteries has become a fundamental technological path that balances high energy density, high safety, and flexible and functional design. Summary of the Invention

[0003] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. Therefore, the object of the present invention is to provide an ionic liquid compound, a solid electrolyte, and a battery.

[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides an ionic liquid compound having the structure shown in Formula I: ; in, It is a 4-8 member nitrogen-containing heterocyclic group; Y - It is an anion.

[0005] In some embodiments, the It is a 5-6 member nitrogen-containing heterocyclic group; the 5-6 member nitrogen-containing heterocyclic group is selected from pyrrole, tetrahydropyrrole, imidazolyl, piperidinyl, and piperazine.

[0006] In some implementations... Selected from , , , , .

[0007] In some embodiments, the anion includes at least one selected from hexafluorophosphate ion, bis(trifluoromethanesulfonyl)imide ion, bis(fluorosulfonyl)imide ion, difluorooxalate-borate ion, and nitrate ion.

[0008] In some embodiments, the ionic liquid compound is selected from the following compounds: , , , , , , , , , , , , , , .

[0009] A second aspect of the present invention provides a method for preparing the aforementioned ionic liquid compound, comprising the following steps: The ionic liquid compound was prepared by methylating the compound of formula II and then reacting it with the metal salt MY via an ion exchange reaction. ; in, The definition is as described above; M is a metal cation.

[0010] In some embodiments, the metal cation includes at least one of silver ions, cuprous ions, and lead ions.

[0011] In some embodiments, the methylation is performed using iodomethane.

[0012] In some embodiments, the methylation reaction temperature is 20-80°C, such as 25-70°C, 30°C, 40°C, 50°C, 60°C, etc.; the methylation reaction time is 8-24h, such as 10h, 12h, 18h, 20h, etc.

[0013] In some embodiments, the reaction temperature of the ion exchange reaction is 15-35°C, such as 20-30°C, 25°C, etc.; the reaction time of the ion exchange reaction is 8-24h, such as 10h, 12h, 18h, 20h, etc.

[0014] A third aspect of the present invention provides a solid electrolyte comprising the aforementioned ionic liquid compound.

[0015] In some embodiments, the solid electrolyte further includes a lithium salt; the mass ratio of the lithium salt to the ionic liquid compound is (1-10):1; such as (2-9):1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, etc.

[0016] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalateborate, lithium dioxalateborate, and lithium nitrate.

[0017] In some embodiments, the water content of the lithium salt is less than 1 ppm.

[0018] In some embodiments, the solid electrolyte further includes a polymer.

[0019] In some embodiments, the polymer monomers of the polymer include at least one of 1,3-dioxopentane and 1,3-dioxane.

[0020] In some embodiments, the solid electrolyte also includes organic additives.

[0021] In some embodiments, the organic additive includes at least one of dimethyl carbonate, ethylene carbonate, vinylene carbonate, ethylene methylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, or diethylene glycol dimethyl ether.

[0022] In some embodiments, the water content of the organic additive is less than 1 ppm.

[0023] In some embodiments, the solid electrolyte is formed by in-situ polymerization of a solid electrolyte precursor; the solid electrolyte precursor includes polymeric monomers, organic additives, lithium salts, and ionic liquid compounds.

[0024] In some embodiments, the solid electrolyte comprises 30-60 wt% polymer, 20-60 wt% organic additives, 5-25 wt% lithium salt, and 0.5-10 wt% ionic liquid compound.

[0025] In some embodiments, the polymer is present in a mass fraction of 30-60 wt%, such as 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, etc.

[0026] In some embodiments, the organic additives account for 20-60 wt% by mass, such as 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, etc.

[0027] In some embodiments, the lithium salt has a mass percentage of 5-25 wt%, such as 8 wt%, 10 wt%, 15 wt%, 18 wt%, 20 wt%, 23 wt%, etc.

[0028] In some embodiments, the ionic liquid compound has a mass percentage of 0.5-10 wt%, such as 0.8 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, etc.

[0029] In some embodiments, the solid electrolyte further includes a support; the support includes at least one of a glass fiber membrane, a polyethylene membrane, a polypropylene membrane, or a cellulose acetate membrane.

[0030] In some embodiments, the solid electrolyte comprises a solid electrolyte precursor formed by in-situ polymerization on a support.

[0031] In some embodiments, the solid electrolyte comprises an in-situ polymerization of monomers and lithium salts in a solid electrolyte precursor to generate a solid electrolyte within a support body. This effectively improves the poor contact between the solid electrolyte and the electrode interface and enhances lithium-ion transport within the electrolyte and battery lifespan.

[0032] In some embodiments, the in-situ polymerization is carried out in an inert atmosphere.

[0033] In some embodiments, the inert atmosphere is provided by an inert gas; the inert gas includes at least one of nitrogen, argon, and xenon.

[0034] In some embodiments, the in-situ polymerization is carried out in an atmosphere with a water content of less than 1 ppm.

[0035] In some embodiments, the in-situ polymerization is carried out in an atmosphere with an oxygen content of less than 1 ppm.

[0036] In some embodiments, the reaction time for the in-situ polymerization is 8-48 hours, such as 12 hours, 24 hours, 36 hours, etc.

[0037] A fourth aspect of the present invention provides a solid-state battery comprising the aforementioned ionic liquid compound or the aforementioned solid electrolyte.

[0038] In some embodiments, the solid-state battery further includes a positive electrode and a negative electrode; wherein a solid electrolyte is spaced between the positive electrode and the negative electrode.

[0039] In some embodiments, the positive electrode includes at least a positive electrode material, a conductive agent, and a binder, wherein the positive electrode active material in the positive electrode material includes LiNi. 0.3 Co 0.3 Mn 0.3 O2, LiNi 0.5 Co 0.3 Mn 0.2 O2, LiNi0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.5 Mn 1.5 At least one of O4.

[0040] In some embodiments, the conductive agent includes at least one of acetylene black (AB), conductive carbon black (Super-P), Ketjen black (KB), carbon nanotubes (CNT), and graphene.

[0041] In some embodiments, the adhesive includes at least one selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polyacrylonitrile, polypropylene carbonate, styrene-butadiene rubber, nitrile rubber, sodium carboxymethyl cellulose, polyethylene oxide, and ethylene oxide-propylene oxide copolymer.

[0042] In some embodiments, the negative electrode comprises lithium metal and / or a lithium metal alloy.

[0043] The beneficial effects of this invention are: The ionic liquid compound of this invention, as an additive, has advantages such as low vapor pressure, wide temperature adaptability, wide electrochemical window, good chemical and electrochemical stability, and environmental friendliness. Furthermore, it can significantly improve battery safety, interface stability, and electrochemical performance, and is beneficial for forming an inorganic-rich electrolyte / electrode interface layer.

[0044] The solid electrolyte of this invention exhibits high lithium-ion conductivity and energy density, excellent electrochemical stability, and interfacial stability, demonstrating superior cycling performance under high pressure. The added ionic liquid enhances the lithium-ion conductivity of the quasi-solid electrolyte and forms a dense, uniform, inorganic-rich interfacial layer on the surface of the lithium metal / (high)nickel cathode material, thereby improving the compatibility between the solid electrolyte and the electrode. The solid electrolyte layer prepared using in-situ polymerization also exhibits wettability and compatibility with the battery electrode materials, facilitating the formation of a dense and uniform CEI / SEI film and significantly improving the electrochemical stability of the battery. Furthermore, the solid electrolyte prepared by in-situ polymerization is easily scalable for industrial production and enables the realization of high-energy-density and high-safety solid-state batteries.

[0045] The solid-state battery of this invention enables the lithium nickel cobalt manganese oxide cathode material to exhibit excellent electrochemical performance at room temperature, specifically: a lithium-ion conductivity of 0.31~0.52 cm⁻¹. -1 After 600 cycles at 4.3V and 1C, the capacity retention rate is 85.9%; after 500 cycles at 4.5V and 1C, the capacity retention rate is 77.5%.

[0046] The solid-state battery preparation method of this invention is simple and easy to operate, with mild reaction conditions, no environmental pollution, and is suitable for mass industrial production. Attached Figure Description

[0047] Figure 1 The room temperature interface impedance curves are for the NCM811 / Li solid-state batteries of Example 3 and Comparative Example 1.

[0048] Figure 2 SEM images of the NCM cathode after cycling of the NCM811 / Li solid-state batteries of Example 3 and Comparative Example 1.

[0049] Figure 3 The room temperature interface impedance curves are for the Li / Li solid-state batteries formed by the solid electrolytes in Example 3 and Comparative Example 1.

[0050] Figure 4 The image shows SEM images of lithium metal after cycling in the Li / Li solid-state batteries formed by the solid electrolytes in Example 3 and Comparative Example 1.

[0051] Figure 5 The cycling curves of the solid lithium metal batteries of Example 3 and Comparative Example 1 after 600 cycles at 4.3V and 1C are shown.

[0052] Figure 6 The cycling curve of the solid lithium metal battery of Example 3 after 500 cycles at 4.5V and 1C is shown. Detailed Implementation

[0053] The present invention will be further described in detail below through specific embodiments. Unless otherwise specified, the raw materials, reagents, or apparatus used in the embodiments and comparative examples are all available from conventional commercial sources or can be obtained by existing technical methods. Unless otherwise specified, the test or experimental methods are conventional methods in the art.

[0054] In this article, "room temperature" or "normal temperature" refers to 25±5℃. Example 1 This embodiment prepares an ionic liquid PyBCNPF6 (1-benzyl-3-cyano-1-methylpyrrolidine hexafluorophosphate), and the specific process is as follows:

[0055] 1 mmol of 1-benzyl-3-acrylonitrile and 5 mL of anhydrous acetonitrile were placed in a flask, and 2 mmol of iodomethane was slowly added. The mixture was stirred at 60 °C for 12 hours. After cooling, 1 mmol of silver hexafluorophosphate was added, and the mixture was stirred at room temperature for 12 hours. The filtrate was filtered, evaporated to dryness, and dried overnight in a vacuum oven to obtain a solid yellow powder.

[0056] Example 2 This embodiment prepares an ionic liquid PyBCNTFSI (1-benzyl-3-cyano-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt), the specific process of which is as follows:

[0057] 1 mmol of 1-benzyl-3-acrylonitrile and 5 mL of anhydrous acetonitrile were placed in a flask, and 2 mmol of iodomethane was slowly added. The mixture was stirred at 60 °C for 12 hours. After cooling, 1 mmol of silver bis(trifluoromethanesulfonyl)imide was added, and the mixture was stirred at room temperature for 12 hours. The filtrate was filtered, evaporated to dryness, and dried overnight in a vacuum oven to obtain a solid brown powder.

[0058] Example 3 This embodiment describes the fabrication of a lithium battery, the specific process of which is as follows: (1) Preparation of electrolyte precursor solution 1,3-Dioxapentane, dimethyl carbonate, and fluoroethylene carbonate were mixed in a glove box at a volume ratio of 5:3:2 to obtain a mixture. Then, lithium salt, lithium hexafluorophosphate (1 mol / L), and lithium difluorooxalate borate (0.2 mol / L) were added to the mixture, followed by 3% PyBCNPF6 additive (by mass of the electrolyte precursor solution). The mixture was thoroughly mixed to ensure complete mixing of the lithium salt, additive, monomer, and solvent, thus obtaining the electrolyte precursor solution.

[0059] (2) Preparation of positive electrode sheet First, lithium nickel cobalt manganese oxide (NCM811) powder, conductive carbon black, and polyvinylidene fluoride binder are mixed evenly in a mass ratio of 8:1:1. Then, N-methylpyrrolidone (solid-liquid ratio of 1:2.5) is added and the mixture is stirred evenly to form a slurry. This slurry is then coated onto aluminum foil and dried in an oven at 770°C for 12 hours. The slurry is then pressed using a tablet press and cut into positive electrode sheets with a diameter of 16 mm. Finally, the sheets are placed in a vacuum drying oven at 80°C for 12 hours, weighed, and stored in a glove box for later use, thus obtaining the positive electrode sheet.

[0060] (3) Assemble the battery First, place the positive electrode sheet in the middle of the negative electrode shell, then place the support, and then drop a few drops of the electrolyte precursor solution from step (1) onto the support. Next, place the lithium sheet, steel sheet, gasket, and positive electrode shell. Finally, use a battery sealing machine to press the battery together, assembling it into a CR2032 button battery. Let it stand for 24 hours to allow for in-situ polymerization, thus obtaining a lithium-ion battery. The electrolyte precursor solution is in-situ polymerized and solidified into a solid electrolyte within the support.

[0061] Example 4 This example provides a lithium-ion battery whose preparation method differs from that of Example 3 only in the content of ionic liquid additives in the electrolyte precursor solution. Specifically: 1,3-Dioxapentane, dimethyl carbonate, and fluoroethylene carbonate were mixed in a glove box at a volume ratio of 5:3:2 to obtain a mixture. Then, lithium salt, lithium hexafluorophosphate (1 mol / L), and lithium difluorooxalate borate (0.2 mol / L) were added to the mixture, followed by 1% PyBCNPF6 additive (based on the mass of the electrolyte precursor solution). The mixture was thoroughly mixed to ensure complete mixing of the lithium salt, additive, monomer, and solvent, thus obtaining the electrolyte precursor solution.

[0062] Example 5 This example provides a lithium-ion battery whose preparation method differs from that of Example 3 only in the content of ionic liquid additives in the electrolyte precursor solution. Specifically: 1,3-Dioxapentane, dimethyl carbonate, and fluoroethylene carbonate were mixed in a glove box at a volume ratio of 5:3:2 to obtain a mixture. Then, lithium salt, lithium hexafluorophosphate (1 mol / L), and lithium difluorooxalate borate (0.2 mol / L) were added to the mixture, followed by 5% PyBCNPF6 additive (based on the mass of the electrolyte precursor solution). The mixture was thoroughly mixed to ensure complete mixing of the lithium salt, additive, monomer, and solvent, thus obtaining the electrolyte precursor solution.

[0063] Example 6 This example provides a lithium-ion battery whose preparation method differs from that of Example 3 only in the content ratio of the electrolyte precursor solution. Specifically: 1,3-Dioxopentapentanol, dimethyl carbonate, and fluoroethylene carbonate were mixed in a glove box at a volume ratio of 6:2:2 to obtain a mixture. Then, lithium salt, lithium hexafluorophosphate (1 mol / L), and lithium difluorooxalate borate (0.2 mol / L) were added to the mixture, followed by 3% PyBCNPF6 additive (based on the mass of the electrolyte precursor solution). The mixture was thoroughly mixed to ensure complete mixing of the lithium salt, additive, monomer, and solvent, thus obtaining the electrolyte precursor solution.

[0064] Example 7 This example provides a lithium-ion battery whose preparation method differs from that of Example 3 only in the lithium salt content of the electrolyte precursor solution. Specifically: 1,3-Dioxapentane, dimethyl carbonate, and fluoroethylene carbonate were mixed in a glove box at a volume ratio of 5:3:2 to obtain a mixture. Then, lithium salt, lithium hexafluorophosphate (1 mol / L), and lithium difluorooxalate borate (0.5 mol / L) were added to the mixture, followed by 3% PyBCNPF6 additive (based on the mass of the electrolyte precursor solution). The mixture was thoroughly mixed to ensure complete mixing of the lithium salt, additive, monomer, and solvent, thus obtaining the electrolyte precursor solution.

[0065] Example 8 This example provides a lithium-ion battery whose preparation method differs from that of Example 3 only in the lithium salt content of the electrolyte precursor solution. Specifically: 1,3-Dioxapentane, dimethyl carbonate, and fluoroethylene carbonate were mixed in a glove box at a volume ratio of 5:3:2 to obtain a mixture. Then, lithium salt, lithium hexafluorophosphate (1 mol / L), and lithium difluorooxalate borate (1 mol / L) were added to the mixture, followed by 3% PyBCNPF6 additive (based on the mass of the electrolyte precursor solution). The mixture was thoroughly mixed to ensure that the lithium salt, additive, monomer, and solvent were fully combined to obtain the electrolyte precursor solution.

[0066] Example 9 This example provides a lithium-ion battery whose preparation method differs from that of Example 3 only in the type of ionic liquid in the electrolyte precursor solution. Specifically: 1,3-Dioxapentane, dimethyl carbonate, and fluoroethylene carbonate were mixed in a glove box at a volume ratio of 5:3:2 to obtain a mixture. Then, lithium salt, lithium hexafluorophosphate (1 mol / L), and lithium difluorooxalate borate (0.2 mol / L) were added to the mixture, followed by 3% PyBCNTFSI additive (based on the mass of the electrolyte precursor solution). The mixture was thoroughly mixed to ensure complete mixing of the lithium salt, additive, monomer, and solvent, thus obtaining the electrolyte precursor solution.

[0067] Comparative Example 1 This example provides a lithium-ion battery whose preparation method differs from that of Example 3 in that the solid electrolyte in this example does not contain ionic liquid additives. Specifically: 1,3-Dioxapentane, dimethyl carbonate, and fluoroethylene carbonate were mixed in a glove box at a volume ratio of 5:3:2 to obtain a mixture. Then, lithium salt, lithium hexafluorophosphate (1 mol / L), and lithium difluorooxalate borate (0.2 mol / L) were added to the mixture and mixed thoroughly to ensure that the lithium salt, additives, monomers, and solvent were fully mixed to obtain an electrolyte precursor solution.

[0068] Test case This experimental example demonstrates the performance testing of a lithium-ion battery. The specific process is as follows: 1. Ionic conductivity test At room temperature, the ionic conductivity of the solid electrolytes in Examples 3-9 and Comparative Example 1 was tested using stainless steel symmetric cells. The specific test results are shown in Table 1 below.

[0069] Table 1

[0070] As shown in Table 1, the solid-state lithium-ion batteries obtained using the solid-state electrolytes of Examples 3-9 of this invention all exhibit high room-temperature ionic conductivity (0.31-0.52 mS·cm). -1 The room temperature ionic conductivity of the solid electrolyte in the present invention is higher than that of the solid electrolyte in Comparative Example 1. Therefore, using the solid electrolyte in the embodiments of the present invention is beneficial to obtaining better battery performance.

[0071] 2. Impedance performance testing and SEM testing The interface impedance performance of the NCM811 / lithium batteries of Examples 3-9 and Comparative Example 1 was tested at room temperature. Figure 1 The table shows the room temperature interface impedance curves of the NCM811 / lithium solid-state batteries of Example 3 and Comparative Example 1. It can be seen that the battery of Example 3 has a smaller interface impedance of 59.3Ω, while the solid-state battery of Comparative Example 1 has a significantly larger interface impedance of 121.6Ω. This indicates that the solid electrolyte of Example 3 has faster lithium-ion transport and better compatibility with lithium nickel cobalt manganese oxide cathode materials. Figure 2 The images show SEM images of the NCM cathodes of Example 3 and Comparative Example 1 after 50 cycles of the NCM811 / Li solid-state batteries. The results indicate that, compared to the particle breakage on the NCM cathode with the electrolyte of Comparative Example 1, the electrolyte in Example 3 effectively protects the stability of the material and exhibits better interfacial compatibility with the high-nickel cathode.

[0072] At room temperature, the interfacial impedance properties of the solid electrolytes in Examples 3-9 and Comparative Example 1 were tested using lithium symmetric batteries. Figure 3 The table shows the room temperature interface impedance curves of the lithium symmetric solid-state batteries formed by the solid electrolytes in Example 3 and Comparative Example 1. Compared with Comparative Example 1, the battery formed by the solid electrolyte in Example 3 has a smaller interface impedance (148.5Ω < 312.1Ω), indicating that the interface compatibility and stability between the solid electrolyte and the lithium anode in Example 3 are improved. Figure 4 The Li / Li solid-state batteries formed using the solid electrolytes in Example 3 and Comparative Example 1 were tested at 0.2 mA cm⁻¹. -2SEM images of lithium metal after cycling at current density for 100 h show that, compared with the moss-like and irregular lithium deposits on the lithium anode with solid electrolyte in Comparative Example 1, the lithium deposits formed by the solid electrolyte in Example 3 exhibit a denser and more uniform morphology, demonstrating better interfacial compatibility with the lithium anode.

[0073] 3. Cyclic performance testing At room temperature, the NCM811 / lithium batteries of Examples 3-9 and Comparative Example 1 were tested for cycling performance at 1C and 4.3V for 600 cycles. Figure 5 The figure shows the cycle curves of the solid-state lithium-ion batteries of Example 3 and Comparative Example 1 after 600 cycles at 1C. As can be seen from the figure, the discharge specific capacity of the solid-state battery of Example 3 is 146.4 mAh·g. -1 The capacity retention rate can reach 85.9%, while the solid-state battery in Comparative Example 1 has a discharge specific capacity of 51.5 mAh·g after 600 cycles. -1 The capacity retention rate was 33.1%, which is far lower than that of Example 3.

[0074] In addition, the cycle performance of the solid-state lithium-ion battery in Example 3 was tested at 1C and 4.5V. Figure 6 The figure shows the cycle curve of the lithium-ion battery of Example 3 after 500 cycles at 1C. As can be seen from the figure, the discharge specific capacity of the solid-state battery of Example 3 is 124.3 mAh·g. -1 After 500 cycles, the capacity retention rate can reach 77.5%, indicating that the solid electrolyte of Example 3 and the NCM811 cathode material have good compatibility at higher voltages.

[0075] In summary, the composite solid electrolytes in Examples 3-9 of this invention not only possess high ionic conductivity (reaching 0.31-0.52 mS·cm at room temperature), but also exhibit high conductivity. -1 Furthermore, it exhibits excellent matching performance with the positive and negative electrodes of solid-state lithium batteries. Moreover, due to the superior ion transport capability of the composite solid-state electrolyte in Examples 3-9, the assembled NCM811 / Li solid-state batteries demonstrate excellent performance at high current and room temperature, and also exhibit good cycle stability at higher voltages. The solid-state electrolyte in Examples 3-9 not only ensures high energy density and safety but also effectively improves the ionic conductivity of the solid-state electrolyte. Furthermore, the solid-state electrolyte forms a better inorganic-rich interface layer in contact with the electrodes, resulting in superior cycle stability.

[0076] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. An ionic liquid compound, characterized in that: It has the structure shown in Equation I: ; in, It is a 4-8 member nitrogen-containing heterocyclic group; Y - It is an anion.

2. The ionic liquid compound according to claim 1, characterized in that: The It is a 5-6 member nitrogen-containing heterocyclic group; the 5-6 member nitrogen-containing heterocyclic group is selected from pyrrole, tetrahydropyrrole, imidazolyl, piperidinyl, and piperazine.

3. The ionic liquid compound according to claim 1, characterized in that: The anion includes at least one of hexafluorophosphate ion, bis(trifluoromethanesulfonyl)imide ion, bis(fluorosulfonyl)imide ion, difluorooxalate-borate ion, and nitrate ion.

4. The ionic liquid compound according to claim 1, characterized in that: The ionic liquid compound is selected from the following compounds: 、 、 、 、 、 、 、 、 、 、 、 、 、 、 。 5. A method for preparing the ionic liquid compound according to any one of claims 1-4, characterized in that: Includes the following steps: The ionic liquid compound was prepared by methylating the compound of formula II and then reacting it with the metal salt MY via an ion exchange reaction. ; in, The definition is as described in any one of claims 1-4; M is a metal cation.

6. A solid electrolyte, characterized in that: Includes the ionic liquid compound according to any one of claims 1-4.

7. The solid electrolyte according to claim 6, characterized in that: The solid electrolyte also includes a lithium salt; the mass ratio of the lithium salt to the ionic liquid compound is (1-10):

1.

8. The solid electrolyte according to claim 6, characterized in that: The solid electrolyte further includes a polymer; the polymer monomer includes at least one of 1,3-dioxopentane and 1,3-dioxane; and / or, the solid electrolyte further includes an organic additive; the organic additive includes at least one of dimethyl carbonate, ethylene carbonate, vinylene carbonate, methylene ethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, or diethylene glycol dimethyl ether.

9. A solid-state battery, characterized in that: It includes the ionic liquid compound according to any one of claims 1-4 or the solid electrolyte according to any one of claims 6-8.

10. The solid-state battery according to claim 9, characterized in that: The solid-state battery also includes a positive electrode and a negative electrode; wherein a solid electrolyte is spaced between the positive electrode and the negative electrode.